Article: Pengalaman Emosional Lelaki Seks Lelaki dalam Menghadapi Upaya yang Dilakukan Setelah Terdiagnosa HIV di Puskesmas Simpang Kawat Kota Jambi Tahun 2019 - Tedy Asharyadi; Budhi Mulyadi; Mahathir Mahathir (Universitas Batanghari Jambi, 2019)
Emotional feeling of men who have sex with men (MSM). This study showed the experience on facing the emotional feeling of men who have sex with man (MSM) after diagnosed having HIV with their partners. This study using qualitative approach with descriptive phenomenology design, the number of participant was 20 people, and getting by in depth interview. Secluding from society often done by people who diagnosed having HIV, asking the information about HIV and how to cure it and getting closer to God for healing. Caring the Men who have sex with man with HIV by more emphaty feeling.